Antimicrobial Drug Resistance in Salmonella enteritidis Isolated From Edible Snakes With Pneumonia and Its Pathogenicity in Chickens - Xia, Ying; Li, Hao; Shen, Yaoqin (Frontiers in Veterinary Science, 2020)
The growing consumption of snakes in China has led to a boom in edible snakes farming. Food producing reptiles, such as snakes can carry many pathogenic microbes and potentially infect humans. Here, we report the occurrence of multi drug resistant Salmonella enteritidis strains isolated from edible snakes in China. Our results showed that the isolated S. enteritidis was resistant to the majority of the tested drugs and sensitive to tetracycline and amikacin. Antimicrobial susceptibility test showed that the strains carried the blaTEM, qnrD, aadA_1, catA_1 o, sulⅠ and sulⅡ genes. The pathogenicity testing of the S. enteritidis isolated strains showed that these strains were highly pathogenic (75% mortality, with LD_50 at 10^7.7CFU/mL). The chickens in the high-dose groups developed acute septicemia and died within 24h. Results of the dissection showed extensive abdominal bleeding and swelling in the high dose groups, as well as hyperemia edema in the livers, lungs, kidneys, cecum and bursa of the chickens, with spotty bleeding. In addition, rod-shaped bacterial aggregation was also seen in the visual field. A total of 23 virulence genes, mainly associated with pathogenicity island were tested, of which 8 genes including avrA, iacP, prgK, ssrA, siiD (spi4D), siiE, spi4H and pipC were found positive. Altogether, our results provide useful information regarding edible snakes contaminated with S. enteritidis, which may have public health implications.